Ethnomedicinal importance of fern and fern allies traditionally used by tribal people of Palani Hills (Kodaikanal), Western Ghats, South India - Thangavelu Muthukumar, Konganapuram Chellappan Ravindran, Ganesan Sathiyaraj, (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Numerous studies have focused on the medicinal properties of angiosperms; however, only limited amount of studies have explored the medicinal potentials of fern and fern allies. The present study focuses on the ethnomedicinal values of fern and fern allies that are traditionally used by the tribal people of Palani hills in South India through a survey of the area. In the present study, information on 50 species belonging to 35 genera in 19 families were recorded for their medicinal values with their botanical name, family, habitat, and manner of using recipes have been recorded.